Aerosol delivery of DNA/liposomes to the lung for cystic fibrosis gene therapy. - Davies, L; Nunez-Alonso, G; McLachlan, G; Hyde, S; Gill, DR (Mary Ann Liebert Inc., 2014)
Abstract Lung gene therapy is being evaluated for a range of acute and chronic diseases, including cystic fibrosis (CF). As these therapies approach clinical realization, it is becoming increasingly clear that the ability to efficiently deliver gene transfer agents (GTAs) to target cell populations within the lung may prove just as critical as the gene therapy formulation itself in terms of generating positive clinical outcomes. Key to the success of any aerosol gene therapy is the interaction between the GTA and nebulization device. We evaluated the effects of aerosolization on our preferred formulation, plasmid DNA (pDNA) complexed with the cationic liposome GL67A (pDNA/GL67A) using commercially available nebulizer devices. The relatively high viscosity (6.3±0.1 cP) and particulate nature of pDNA/GL67A formulations hindered stable aerosol generation in ultrasonic and vibrating mesh nebulizers but was not problematic in the jet nebulizers tested. Aerosol size characteristics varied significantly between devices, but the AeroEclipse II nebulizer operating at 50 psi generated stable pDNA/GL67A aerosols suitable for delivery to the CF lung (mass median aerodynamic diameter 3.4±0.1 μm). Importantly, biological function of pDNA/GL67A formulations was retained after nebulization, and although aerosol delivery rate was lower than that of other devices (0.17±0.01 ml/min), the breath-actuated AeroEclipse II nebulizer generated aerosol only during the inspiratory phase and as such was more efficient than other devices with 83±3% of generated aerosol available for patient inhalation. On the basis of these results, we have selected the AeroEclipse II nebulizer for the delivery of pDNA/GL67A formulations to the lungs of CF patients as part of phase IIa/b clinical studies.